Greece : Fourth Review Under the Extended Arrangement Under the Extended Fund Facility, and Request for Waivers of Applicability and Modification of Performance Criterion-Staff Report; Staff Statement; Press Release; and Statement by the Executive Director for Greece. (IMF Staff Country Reports; Country Report, 2013)
This paper discusses Greece's Fourth Review Under the Extended Arrangement under the Extended Fund Facility, and Request for Waivers of Applicability and Modification of Performance Criterion. The economy is rebalancing, but it continues to do so through recession, not productivity-enhancing structural reform. Domestic demand continues to fall albeit at a moderating pace, and import compression has resulted in a further shrinking of the current account deficit. The large output gap and high unemployment rate are exerting downward pressure on wages, and the competitiveness gap in unit labor cost terms has narrowed further. Product prices are also easing. Sentiment indicators have improved, but the political crisis has had a dampening effect.